2006
DOI: 10.2176/nmc.46.379
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Unruptured Giant Cerebral Aneurysms

Abstract: The long-term outcome of 39 patients with unruptured giant aneurysm (À2.5 cm) treated during the last 12 years was retrospectively reviewed. The 7 male and 32 female patients, aged 32 to 81 years, presented with symptoms related to compression of the surrounding structures by the aneurysm in 28 cases, cerebral infarction in one, and asymptomatic in 10. The locations were the internal carotid artery (ICA) in 27 cases, middle cerebral artery in three, anterior cerebral artery in one, and basilar artery in eight.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 21 publications
1
29
0
2
Order By: Relevance
“…August 2015 patients 224 and for all patients with regard to mortality, but at a cost in terms of morbidity: In a series of 39 patients with giant UIAs, Nakase et al 225 noted that mortality was markedly reduced by surgical intervention (4% versus 31%), but morbidity affected 19% compared with 8% of untreated patients.…”
Section: Strokementioning
confidence: 99%
“…August 2015 patients 224 and for all patients with regard to mortality, but at a cost in terms of morbidity: In a series of 39 patients with giant UIAs, Nakase et al 225 noted that mortality was markedly reduced by surgical intervention (4% versus 31%), but morbidity affected 19% compared with 8% of untreated patients.…”
Section: Strokementioning
confidence: 99%
“…Twenty-one studies reported risk factors for aneurysm growth, including 3954 patients with 4990 aneurysms with 11,000 patient-years and 13,294 aneurysm-years of follow-up. 9,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Eleven of these studies reported the rupture rate of growing aneurysms. Mean patient follow-up was 4.9 years, and median was 3.2 years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 ) [1, . Patient data description was aggregate in 15 study populations (854 GIA) [1,[15][16][17][18][19][20][21][22][23][24][25][26] and individual in 49 study populations (415 GIA) . Table 1 [67] 2002 R E 7 100 50.6 Yes Yes P = Prospective; R = retrospective; S = surgical; E = endovascular; C = combined; N/A = not available.…”
Section: Resultsmentioning
confidence: 99%